Karakteristik Nata De Cacao Dalam Kemasan Cup Plastik Dan Pendugaan Umur Simpannya Dengan Metode Extended Storage Studies - Otik Nawansih; Berti Liansa; Puspita Yuliandari; Susilawati Susilawati; Esa Ghanim Fadhallah (Jurnal Penelitian Pertanian Terapan, 2025)
Nata de cacao has the potential to be packaged in plastic cups as a type of ready-to-consume product. However, its characteristics and shelf life was not yet known. This study aims to determine the characteristics of nata de cacao products in plastic cup packaging and to determine their shelf life. Estimation of the shelf life of nata de cacao products in plastic cup packaging using the Extended Storage Studies (ESS) Method with two treatments, namely without preservatives and with sodium benzoate preservatives. Freshly harvested nata sheets were soaked, washed, diced, boiled in syrup with treatments without adding Na-benzoate and adding Na-benzoate 0.75 g / l, put in a plastic cup and closed. A total of 10 cups of nata without preservatives were stored for 10 days and observed every day, while 10 cups of nata with preservatives were stored for 33 days and observed every 3 days. Sensory observations were carried out by 8 trained panel members including changes in color, appearance and consistency of syrup, aroma and texture of nata. In addition, pH measurements were also carried out. The results of the study showed that the characteristics of nata de cocoa in syrup packed in plastic cups were close to white in color, chewy texture, clear and non-slimy syrup, and non-sour aroma. However, during storage there tended to be a decline. Based on the consumer acceptance limit for the observed parameters, the nata de cocoa product in syrup without preservatives and packed in plastic cups had a shelf life of 5 days at room temperature. While with the addition of 0.75 g/l sodium benzoate preservative, it had a shelf life of 27 days.